PENGARUH KUALITAS LAYANAN DAN KUALITAS PRODUK BSI MOBILE BANKING TERHADAP KEPUASAN NASABAH PADA MAHASISWA FEBI UIN SULTHAN THAHA SAIFUDDIN JAMBI ANGKATAN 2020 - Royan Brata Kusuma; Bambang Kurniawan; Eri Nofriza (MARGIN: Journal of Islamic Banking, 2025)
This study aims to analyze the influence of service quality and product quality of BSI Mobile Banking on customer satisfaction, particularly among students of the Faculty of Economics and Islamic Business (FEBI) at UIN Sulthan Thaha Saifuddin Jambi, class of 2020. This research employs a quantitative approach with a survey method. The study population consists of FEBI UIN Sulthan Thaha Saifuddin Jambi students, class of 2020, who have used BSI Mobile Banking. The sample was determined using a purposive sampling technique, with data collected through questionnaires distributed to 83 respondents. Data analysis was conducted using multiple linear regression tests to measure the effect of the independent variables (service quality and product quality) on the dependent variable (customer satisfaction). The results indicate that both service quality and product quality of BSI Mobile Banking significantly influence customer satisfaction. Good service quality, characterized by responsiveness and reliability, as well as product quality that meets user expectations, can increase customer satisfaction. However, some issues related to limited features and technical disruptions still affect the satisfaction levels of some users